The Impact of Particulate Matter (PM2.5) on Human Retinal Development in hESC-Derived Retinal Organoids - Zeng, Yuxiao; Li, Minghui; Zou, Ting; Chen, Xi; Li, Qiyou; Li, Yijian; Ge, Lingling; Chen, Siyu; Xu, Haiwei (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidences demonstrated that PM2.5 could cross the placenta and fetal blood brain barrier, causing neurotoxicity of embryonic development. The retina, an embryologic extension of the central nervous system, is extremely sensitive and vulnerable to environmental insults. The adverse effects of PM2.5 exposure on the retina during embryonic neurodevelopment is still largely unknown. Our goal was to investigate the effect of PM2.5 on human retinal development, which was recapitulated by human embryonic stem cells (hESCs) derived retinal organoids (hEROs). In the present study, using the hEROs as the model, the influences and the mechanisms of PM2.5 on the developing retina was analyzed. It demonstrated that the formation rate of hEROs-derived neural retina (NR) was affected by PM2.5 in a concentration dosage-dependent manner. And the areas of hEROs and the thickness of hERO-NRs were significantly reduced after PM2.5 exposure at the concentration of 25, 50 and 100 µg/ml, which was due to the decrease of proliferation and the increase of apoptosis. Although we did not spot significant effects on retinal differentiation, PM2.5 exposure did lead to hERO-NR cells disarranging and structural disorder. Transcriptome analysis showed that PM2.5 treatment was significantly associated with the mitogen activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/AKT pathways and thus reduced the level of the fibroblast growth factors (FGFs), particularly FGF8 and FGF10. These results provided evidences that PM2.5 exposure potentially inhibited proliferation and increased apoptosis at the early development stage of human neural retina, probably through MAPK and PI3K/Akt pathway. Our study suggested that exposure to PM2.5 suppressed the cell proliferation and promoted cells apoptosis whereby contributed to abnormal human retinal development.